Novel thiobarbiturates as potent urease inhibitors with potential antibacterial activity: Design, synthesis, radiolabeling and biodistribution study. Issue 23 (1st December 2020) - Abdulwahab, Hanan Gaber; Harras, Marwa F.; El Menofy, Nagwan Galal; Hegab, Amany M.; Essa, Basma M.; Selim, Adli AbdAllah; Sakr, Tamer M.; El-Zahabi, Heba S.A.
Graphical abstract: Highlights: Novel thiobarbiturate derivatives were synthesized as urease inhibitors. Anti-urease and antibacterial activities were investigated. Compound 4 was the most potent. Biodistribution study of radiolabeled 99m Tc-compound 4 revealed a remarked uptake into infection induced in mice. Molecular docking analysis was also performed. Abstract: Urease enzyme is a virulence factor that helps in colonization and maintenance of highly pathogenic bacteria in human. Hence, the inhibition of urease enzymes is well-established to be a promising approach for preventing deleterious effects of ureolytic bacterial infections. In this work, novel thiobarbiturate derivatives were synthesized and evaluated for their urease inhibitory activity. All tested compounds effectively inhibited the activity of urease enzyme. Compounds 1, 2a, 2b, 4 and 9 displayed remarkable anti-urease activity (IC50  = 8.21–16.95 μM) superior to that of thiourea reference standard (IC50  = 20.04 μM). Moreover, compounds 3a, 3g, 5 and 8 were equipotent to thiourea. Among the tested compounds, morpholine derivative 4 (IC50  = 8.21 µM) was the most potent one, showing 2.5 folds the activity of thiourea. In addition, the antibacterial activity of the synthesized compounds was estimated against both standard strains and clinical isolates of urease producing bacteria. Compound 4 explored the highest potency exceeding that of cephalexin reference drug. Moreover, biodistribution study using radiolabeling approach revealed a remarked uptake of 99m Tc-compound 4 into infection induced in mice. Furthermore, a molecular docking analysis revealed proper orientation of title compounds into the urease active site rationalizing their potent anti-urease activity.